ENHANCING COLLABORATIVE SKILLS IN ELEMENTARY SCHOOL: A DIFFERENTIATED LEARNING FOCUS - Ramli; Siskika Nalati Lova (JURNAL STRATEGI PEMBELAJARAN, 2025)
Differentiated learning combines the process, learning styles, and interests of students by considering the process, product, and content. This study explores the practice of differentiated learning in Islamic elementary schools in Mataram City. Data was collected using a qualitative approach through interviews, observations, and documentation. The study's results illustrate that the practice of differentiated learning goes through four stages: diagnostic assessment, planning, implementation, and evaluation of the implementation of learning. Diagnostic assessments are carried out to obtain an initial picture of students' potential and development, which is carried out through quizzes. Furthermore, at the planning stage, the school analyzes the suitability of the content with the process, product, and interests of the students. Meanwhile, at the implementation stage, teachers are guided by planning, and ultimately, these four stages can build students' collaboration skills. Collaboration skills are shown by the ability to cooperate between colleagues and groups, with a spirit of working together to overcome and clarify misunderstandings